AS MUDANÇAS CLIMÁTICAS FUTURAS PODEM FAVORECER A EXPANSÃO DA ESPÉCIE ADENIUM OBESUM (FORSSK.) ROEM. & SCHULT? - FLECK, Izabel Melz; BUENO, Marcelo Leandro; OLIVEIRA, Samara Fernanda de; PONTARA, Vanessa (ANAIS DO ENIC, 2024)
-